Transposon-associated epigenetic silencing during Pleurotus ostreatus life cycle. (8th June 2018) - Borgognone, Alessandra; Castanera, Raúl; Morselli, Marco; López-Varas, Leticia; Rubbi, Liudmilla; Pisabarro, Antonio G; Pellegrini, Matteo; Ramírez, Lucía
Abstract: Transposable elements constitute an important fraction of eukaryotic genomes. Given their mutagenic potential, host-genomes have evolved epigenetic defense mechanisms to limit their expansion. In fungi, epigenetic modifications have been widely studied in ascomycetes, although we lack a global picture of the epigenetic landscape in basidiomycetes. In this study, we analysed the genome-wide epigenetic and transcriptional patterns of the white-rot basidiomycete Pleurotus ostreatus throughout its life cycle. Our results performed by using high-throughput sequencing analyses revealed that strain-specific DNA methylation profiles are primarily involved in the repression of transposon activity and suggest that 21 nt small RNAs play a key role in transposon silencing. Furthermore, we provide evidence that transposon-associated DNA methylation, but not sRNA production, is directly involved in the silencing of genes surrounded by transposons. Remarkably, we found that nucleus-specific methylation levels varied in dikaryotic strains sharing identical genetic complement but different subculture conditions. Finally, we identified key genes activated in the fruiting process through the comparative analysis of transcriptomes. This study provides an integrated picture of epigenetic defense mechanisms leading to the transcriptional silencing of transposons and surrounding genes in basidiomycetes. Moreover, our findings suggest that transcriptional but not methylation reprogramming triggers fruitbody development in P. ostreatus.